EDUKASI MANFAAT NUTRISI BAGI TUMBUH KEMBANG GIGI DAN MULUT ANAK USIA PRA SEKOLAH PADA MURID TK ADZKIA III DI KOTA PADANG - Gita Dwi Jiwanda Sovira; Wulandani Liza Putri; Nila Kasuma (BULETIN ILMIAH NAGARI MEMBANGUN, 2024)
Children's dental health is very important to ensure the child's nutritional status, speaking ability and attractive appearance. Nutrition, diet and dental health in children are closely related, especially in children who are in the growth and development phase. Good quality and proper nutrition is very important to support dental health. Likewise, dental health is also important for adequate nutritional intake. If the teeth and mouth are healthy, then nutritional intake will be optimal, and if nutrition is optimal then the growth and development of the teeth and mouth will also be optimal. As many as 89% of children in Indonesia suffer from dental disease. A number of surveys show that more than a third of the toddler population has experienced toothache and one sixth of them have had at least one tooth extracted. The growth and development of teeth is influenced by nutrition. Healthy dentition will occur if all nutritional elements are available in sufficient quantities. The aim of the activity: to provide education to young children about the importance of nutrition for the growth and development of teeth and mouth. The activity method used is the tell-show-do method with presentations using power point media, posters, models of teeth and toothbrushes, as well as examination of children's teeth and mouths. This method is one of the most appropriate methods for providing education to early childhood. Results of the activity: increased knowledge of children and the emergence of a sense of courage when having a dental examination by a dentist. Conclusion: This activity has a positive impact on young children because children understand better that there is a connection between nutrition and oral health.